Methane emissions from Nellore bulls on pasture fed two levels of starch-based supplement with or without a source of oil - Jose Neto, A. [UNESP]; Messana, J. D. [UNESP]; Rossi, L. G. [UNESP]; Carvalho, I. P.C. [UNESP]; Berchielli, T. T. [UNESP] (CSIRO Publishing, 2018)
Methane emissions (CH4) from enteric fermentation represent an energy loss to the animal ranging from 2% to 12% of gross energy (GE) intake therefore, the challenge is to develop diets and handling strategies to mitigate CH4 emissions. This study tested the hypothesis that fat supplementation as a source of energy could reduce CH4 emissions without decrease animal production, independently of the starch level utilised. Thus, the goal of this study was to assess the combined effects of high- or low-starch supplements with or without a source of oil (soybean grain) on intake, digestibility, performance, and CH4 emissions of finishing Nellore bulls [n = 44 initial bodyweight (BW) = 414 ± 12 kg age of 20 months] grazing on Brachiaria brizantha cv. Xaraés during the dry season. No interactions between starch level and oil source (soybean grain) supplementation with respect to intake of dry matter (DM), forage DM, supplement DM, organic matter (OM), crude protein (CP), neutral detergent fibre (NDF), ether extract (EE), or GE were found. However, there was an effect of starch and oil source on intake of EE. There were no interactions between starch level and oil source supplementation with respect to digestibility of DM, OM, NDF, CP, EE, or digestibility energy. Irrespective of the starch level utilised, the addition of soybean grain (oil source) decreased the digestibility of NDF and increased the digestibility of EE. In relation to animal performance, there were no interactions between starch level and oil regarding initial BW, final BW, average daily gain (ADG), gain efficiency, hot carcass weight, dressing, carcass gain, fat depth, or longissimus muscle area. However, the addition of soybean grain (oil source) increased the fat depth independently of the starch level used. There was no interaction between starch-based supplementation level and oil source on CH4 emissions when expressed in g/day, g/kg DM intake, g/kg OM intake, g/kg NDF intake, % of GE intake, g/g EE intake, g/kg ADG, or g/kg of carcass gain. Therefore, the addition of soybean grain (oil source) in supplements, independent of starch level used, was associated with reduced CH4 emissions expressed in g/day. Additionally, soybean grain (oil source) decreased enteric CH4 emissions relative to GE and EE intake and ADG for animals fed high- or low-starch supplements. Soybean grain supplementation is effective at reducing enteric CH4 emissions from Nellore bulls grazing on tropical pasture.
Keywords: concentrates; forage; greenhouse gases; ruminant